The effect of physical evidence and service on air conditioner purchase decision - Diya, Octa Dwi; Ahmad, Aripin (Lighthouse Publishing, 2025)
The business world is experiencing very tight trade competition which makes business people have to carry out the right marketing strategy. In the context of marketing management, it is important to understand that an effective strategy not only involves managing company resources and activities, but also requires a deep understanding of consumer behavior. CV Redy Teknik in Bandar Lampung is required to increase physical evidence factors and provide good service so that there can be an increase in purchasing decisions. For this reason, this study raises the problem of whether physical evidence and service variables have the same influence on purchasing decisions by CV Redy Teknik in Bandar Lampung. The hypothesis in this study is that there is a positive and significant influence between Physical Evidence and Service on Air Conditioner Purchasing Decisions at CV Redy Teknik in Bandar Lampung. The data collection method used was a questionnaire with a sample of 100 customers. The results of the discussion with the multiple regression analysis model obtained the results that there was a significant influence. This is evidenced by the results of the F test to determine the influence of independent variables together on the decision to purchase air conditioners at CV Redy Teknik in Bandar Lampung, the calculated significance value was obtained at 0.000, in other words, the value is smaller than the research alpha value of 5%. Partially, testing was carried out using the t test, with the value of each independent variable influencing the dependent variable of the purchasing decision of CV Redy Teknik in Bandar Lampung. Thus, the formulated hypothesis can be said to be tested.